A Reconsideration of the Chronology of a Decree of Abdera (Syll.3 656) and the Introduction of the concept of Roman Patronage to the Greeks in the Second Century BC. (November 2021) - Ito, Masayuki
Abstract: Roman patronage was known to the Greeks in various contexts even in the period of the Third Macedonian War. The reference to it in an Abderan decree ( Syll . 3 656) can be dated to the 160s BC as part of this process. Although this date is chronologically isolated from the other instances of the term πάτρων in Greek inscriptions, in the light of our historical sources as a whole it is reasonable to treat Syll . 3 656 as evidence of how the Greeks were gradually trying to respond to Roman culture and institutions through changes in their own language and terminology even before the period when Rome ruled them directly. Supplementary material is available online and comprises two appendices (https://doi.org/10.1017/S0075426921000033 ).